Magnetite‐graphene oxide sheets as support for hemimicelles/admicelles based microextraction of acidic, basic and neutral compounds prior to gas chromatography determination. Issue 12 (21st October 2019) - Nazari, Najmeh; Masrournia, Mahboubeh; Es'haghi, Zarrin; Bozorgmehr, Mohammad‐Reza
Abstract: Simultaneous extraction of basic, acidic and neutral compounds is an important goal in sample preparation. In this study, dispersive solid‐phase microextraction of three analyte types was carried out in a single step. The target compounds: aniline, phenol and naphthalene with surfactant modified magnetic graphene oxide sheets, before gas chromatography with flame ionization detection. The dispersive solid‐phase microextraction performed in both cationic and anionic modes by cetyltrimethylammonium bromide and sodium dodecyl sulfate respectively. First, the analytes were vortexed and adsorbed then the supernatant was decanted with a magnet and the sorbent was eluted with the proper solvent. The linearity was obtained over a wide concentration range; 0.044–0.50, 0.043–0.50 and 0.027–0.25 µg/mL for aniline, phenol and naphthalene respectively in both modes. The limit of detection and the limit of quantitation for target analytes were 0.008 –0.02 and 0.027–0.067 µg/mL, respectively in both modes. The method relative standard deviations for the analytes (0.1 µg/mL conc.) were ranged from 4.0 to 10.9% (n = 10). Enrichment factors ranged from 60 to 373. The method was successfully evaluated to simultaneously extract three different types of analytes (basic, acidic and neutral) from water samples. The recoveries ranged from 90.0 to 100.0%.